Perkembangan, Problematika dan Kebijakan Sistem Pendidikan di Malaysia - Ummi Kalsum; Lidia Napida; Dwi Noviani; Zainuddin Zainuddin (CV. Aksara Global, 2023)
This article provides a good understanding of the background, system, curriculum and problems in Islamic education in Malaysia. There are several important points in this article, namely about the background of Islamic education in Malaysia: The history of the arrival of Islam to Malaysia in the 14th century and its main role in society after the arrival of the Malays explains the roots of Islamic education in Malaysia. The presence of Islamic scholars and scholars in Islamic preaching in Malaysia reflects the importance of religious education in the culture and history of the country; Development of Islamic Education in Malaysia: this article details the development of Islamic education in Malaysia in three periods: the early period, the period of British rule, and the period after independence. These include the introduction of Islamic education subjects in public schools after independence and the establishment of Islamic higher education institutions; Islamic Education System in Malaysia: explains the structure of the Islamic education system in Malaysia, including its stages such as pre-school, primary, secondary, and pre-university education. An explanation of exams and qualifications also provides a good understanding of how students move through the education system. ; Educational Curriculum in Malaysia: The educational curriculum in Malaysia is explained with a focus on subjects, tests, and language of instruction; outlines changes in curriculum over time and the emphasis on languages of instruction, including English, in education; Problems and Policies in the Education System: covers several problems facing the Malaysian education system, such as access gaps, ethnic issues, and language of instruction. The government has responded with policies such as scholarship programs, skills-based education, and improved teacher training; Policies in the Education System: A number of policies that have been implemented in Malaysia, such as the Basic National Education and skills-based education programs, are also described in this paper providing a good view of the evolution and challenges of Islamic education in Malaysia as well as the government's efforts to overcome existing problems. . This is important to understand how Islamic education plays a role in Malaysia's multicultural and multiethnic society.